Application of autonomous vehicles in maritime industry - Tan, Isaac (Nanyang Technological University, 2021)
The adoption of autonomous vehicles in the maritime industry is affected by a myriad of factors. In this report, I investigated factors that are deemed as the most important in the encouragement or hindrance of the adoption of autonomous vehicle technology in the maritime industry excluding the technological availability and costs which have been tackled in volume 1 and 3 respectively. By conducting interviews with several maritime professionals, I distilled the factors that they believe should be taken into consideration when deliberating the adoption of autonomous vehicles in the industry. In the literature review, I identified that safety, politics, and social acceptance are the main factors affecting the adoption of autonomous vehicles on public roads. I evaluated that these factors are applicable to adoption of autonomous vehicles in the maritime industry, even though the reasons behind the factors are different. The main factors brought up in my study are the following, ranked in their order of importance: Insurance and Liabilities, Regulations, Supporting Infrastructure, Labour Issues, Technical Readiness, Safety, Productivity, Cyber Security and Government Support. These factors were ranked based on the number of interviews where these topics were mentioned. The more times a topic was mentioned, the higher order of importance it is deemed to possess. I recommended that when studying autonomous vehicles in the maritime industry, one should look at factors specific to the maritime industry. This is because only some factors that apply to general autonomous vehicles are applicable to the maritime industry. I also explained how certain factors require industry-wide collaboration, and thus, it is not easy to recommend a solution for the higher order factors such as regulations and insurance. Nonetheless, knowing that supporting infrastructure is one of the important factors, I suggested that countries invest in supporting infrastructure to facilitate the adoption of autonomous vehicles in the industry. In addition, governments must provide adequate support for the training of skilled labour for the industry in the maintenance and technical support of the autonomous vehicles. As part of a broader report investigating autonomous vehicle adoption in the maritime industry, this section will enable readers to understand industry specific considerations in maritime on the adoption of autonomous vehicles.